PERSEPSI MASYARAKAT TENTANG KEBIJAKAN PEMBERIAN VAKSINASI COVID-19 DI DESA SEJANGAT KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Tiara Romadhani; Nurhamlin ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The Covid-19 vaccination policy is a problem among the people. Differences in perceptions among the public give rise to pros and cons. This is influenced by differences in mindset and perspective of the community towards Covid-19 vaccination. Community understanding regarding this arises because of positive and negative influences, namely experiences that people see and feel such as lots of news and exposure to social media so that it has a positive or negative impact on the implementation of vaccination carried out in various regions, especially in research locations, namely villages. Sincerely. The aim of the research is to analyze the problems in the implementation of the Covid-19 vaccination among the public which give rise to positive and negative perceptions that lead to the pros and cons by using the theory of Innovation and the theory of Environmental Psychology. The research location was in Sejangat Village, Bukit Batu District, Bengkalis Regerency using descriptive qualitative methods through interview, observation, documentation, and triangulation data collection techniques. The results of the study indicate that public perception of the Covid-19 vaccination policy is more positive than negative so that in general it can be well received among the community besides that public acceptance of the Covid-19 vaccination policy is classified as high based on the category of Innovators, Early Users, End Users, Early Majority, Late Majority, and Laggard which shows that the Innovator group is more than the other group categories. Keywords: Vaccination, Perception, Innovation.